2008
DOI: 10.1007/s12264-008-0096-4
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference mediated silencing of α-synuclein in MN9D cells and its effects on cell viability

Abstract: ObjectiveTo silence the expression of -synuclein in MN9D dopaminergic cells using vector mediated RNA interference (RNAi) and examined its effects on cell proliferation and viability. Methods We identified two 19-nucleotide stretches within the coding region of the -synuclein gene and designed three sets of oligonucleotides to generate doublestranded (ds) oligos. The ds oligos were inserted into the pENTR TM /H1/TO vector and transfected into MN9D dopaminergic cells. -Synuclein expression was detected by RT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…In neuronal cells, similar to that used in our experiments, it has been demonstrated that downregulation of SNCA had a specific effect on viability, but not proliferative potential (Liu et al 2008). Elevation of SNCA by inhibition of HDAC increases neuronal protection against death induced by glutamate (Leng and Chuang 2006) or 6-OHDA (Monti et al 2007).…”
Section: Discussionsupporting
confidence: 64%
“…In neuronal cells, similar to that used in our experiments, it has been demonstrated that downregulation of SNCA had a specific effect on viability, but not proliferative potential (Liu et al 2008). Elevation of SNCA by inhibition of HDAC increases neuronal protection against death induced by glutamate (Leng and Chuang 2006) or 6-OHDA (Monti et al 2007).…”
Section: Discussionsupporting
confidence: 64%
“…In support of this, a recent report showed that specifically silencing endogenous rat SNCA in vivo in substantia nigra with an shRNA approach resulted in loss of DA neurons (Gorbatyuk et al, 2010). Another study showed that down-regulation of SNCA in MN9D cells decreases cell viability (Liu et al, 2008). On the other hand, it was recently reported that down regulation of endogenous SNCA in primate substantia nigra by pump delivery of siRNAs does not reduce the number and phenotype of nigral DA neurons (McCormack et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a-syn null mice do not develop a nigrostriatal lesion (Abeliovich et al, 2000). This plausible therapeutic approach was applied with RNAi to reduce the synthesis in vitro and in vivo (Fountaine and Wade-Martins, 2007;Liu et al, 2008;Sapru et al, 2006). To date, studies have yielded conflicting results regarding the effectiveness and tolerability of this strategy, with different groups reporting nigrostriatal degeneration (Gorbatyuk et al, 2010;Khodr et al, 2011Khodr et al, , 2014 and deleterious inflammation (Khodr et al, 2014) after depleting a-syn in the rat brain.…”
Section: Parkinson's Disease Therapeutic Approachesmentioning
confidence: 99%